Effectiveness Of KPI To Improve Operational Performance Of Pt JIEP Company - Nur Az Zahra Divva Kharisma; Al Hasin (Cita konsultindo, 2025)
PT Jakarta Industrial Estate Pulogadung is the manager of the Jakarta industrial area and is committed to developing a modern and sustainable industrial area. PT Jakarta Industrial Estate Pulogadung (PT JIEP) as the manager of a strategic industrial area in Jakarta faces challenges in increasing productivity and operational efficiency. PT Jakarta Industrial Estate Pulogadung as the manager of a strategic industrial area in Jakarta faces challenges in increasing productivity and operational efficiency. However, to overcome this, PT Jakarta Industrial Estate Pulogadung in 2020 PT JIEP began using key performance indicators. The data used in this study came from observations, interviews, and data on the prognosis of the achievement of PT Jakarta Industrial Estate Pulogading's KPI in 2024. At PT Jakarta Industrial Estate Pulogadung, the biggest causes of KPI not being achieved were